Ti6Al4V Nanotubes Filled with Silver Nanoparticles as a Possible Antibacterial Surface for Implants - Průchová, Eva; Kosová, Michaela; Jarolímová, Petra; Joska, Luděk; Hybášek, Vojtěch (Manufacturing Technology Journal, 2018)
The presented work was focused on the use of Ti6Al4V alloy with nanostructured surface and deposited silver nanoparticles as a material with antibacterial surface. Thanks to the electrochemically formed nanotubular oxide structure, a large area was available for silver deposition. Silver was photo-reduced from the silver nitrate solution. The ultrasonic treatment allowed the penetration of a silver source electrolyte into the whole depth of the tubes. Transmission electron microscopy images confirmed the presence of silver nanoparticles with size from units of nanometers up to 15 nm. Nanosilver was present throughout the length of the nanotubes. Samples with photo-reduced silver will be able to provide antibacterial activity not only in critical hours after implantation but also in the longer term due to the subsequent release of silver from the volume of nanotubes. The prolonged antibacterial effect has been demonstrated against Staphylococcus aureus.
Keywords: Titanium; Nanostructure; Nanosilver; Antibacterial; Photo-reduction